2023
DOI: 10.1002/mma.9024
|View full text |Cite
|
Sign up to set email alerts
|

Traveling wave and general form solutions for the coupled Higgs system

Abstract: In this study, the coupled Higgs system, which is a special case of the coupled Higgs field equation, which is effective in energy transport in the sub-particles of the atom, is discussed. With the help of the modified generalized exponential rational function method, which is an important instrument in obtaining traveling wave solutions, both the propagating wave solutions and general form solutions of coupled Higgs system are presented. These solutions are examined under some restrictive conditions as they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 71 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…In order to better understand and explain the nonlinear phenomena, finding exact solutions to the NPDEs has become an important focus of scholars' attention and research. In the past half century, mathematicians and physicists have been dedicated to studying exact solutions to NPDEs, including the Jacobi elliptic function expansion approach [12], modified generalized exponential rational function method [13], direct algebraic approach [14], (G'/G 2 )-expansion method [15], variational approach [16], trial-equation technique [17,18], Bäcklund transformation approach [19,20], subequation approach [21,22], Darboux transformation technique [23,24], exp-function approach [25], modified Kudryashov method [26], extended F-Expansion approach [27], sinh-Gordon equation expansion method [28] and so on. Although mathematical physicists have developed a large number of methods, it has been found that, due to the diversity and complexity of NPDEs, there is currently no unified method to solve them, and often only the corresponding methods can be selected based on specific equations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand and explain the nonlinear phenomena, finding exact solutions to the NPDEs has become an important focus of scholars' attention and research. In the past half century, mathematicians and physicists have been dedicated to studying exact solutions to NPDEs, including the Jacobi elliptic function expansion approach [12], modified generalized exponential rational function method [13], direct algebraic approach [14], (G'/G 2 )-expansion method [15], variational approach [16], trial-equation technique [17,18], Bäcklund transformation approach [19,20], subequation approach [21,22], Darboux transformation technique [23,24], exp-function approach [25], modified Kudryashov method [26], extended F-Expansion approach [27], sinh-Gordon equation expansion method [28] and so on. Although mathematical physicists have developed a large number of methods, it has been found that, due to the diversity and complexity of NPDEs, there is currently no unified method to solve them, and often only the corresponding methods can be selected based on specific equations.…”
Section: Introductionmentioning
confidence: 99%